2003
DOI: 10.5034/inquiryjrnl_40.1.6
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Hospital Industry Restructuring and the Hospital Safety Net

Abstract: The U.S. hospital industry was reshaped during the 1990s, with many hospitals becoming members of health systems and networks. Our research examines whether safety net hospitals (SNHs) were generally included or excluded from these arrangements, and the factors associated with their involvement. Our analysis draws on the earlier work of Alexander and Morrisey (1988), and not only studies factors affecting SNH participation in multihospital arrangements but also updates their earlier study. We constructed measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Researchers have used various methods to identify SNHs, with some focusing exclusively on public hospitals (Marquis, Rogowski, and Escarce ), others on public hospitals and academic medical centers (Baxter and Mechanic ; Fishman and Bentley ), and still others using hospital data on uncompensated or Medicaid care to assess hospital safety net involvement (Cunningham and Tu ; Zuckerman et al. ; Bazzoli, Manheim, and Waters ; Bazzoli et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have used various methods to identify SNHs, with some focusing exclusively on public hospitals (Marquis, Rogowski, and Escarce ), others on public hospitals and academic medical centers (Baxter and Mechanic ; Fishman and Bentley ), and still others using hospital data on uncompensated or Medicaid care to assess hospital safety net involvement (Cunningham and Tu ; Zuckerman et al. ; Bazzoli, Manheim, and Waters ; Bazzoli et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Although this may happen at the margins (e.g., hospitals near the SNH threshold), Bazzoli et al. (), Bazzoli, Manheim, and Waters () found that about three‐quarters of SNHs identified using a similar approach were identified as SNHs 3 years later.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with Bamezai et al (1999), who found that HMO penetration reduced hospital cost growth by the greatest amount in the most competitive hospital markets. Finally, since county economic and demographic factors may affect demand for a hospital's services, county per capita income, the percentage of population aged 65 or older, and total beds per 1,000 population are included in the model Sari 2002;Bazzoli, Manheim, and Waters 2003).…”
Section: Control Variablesmentioning
confidence: 99%
“…Various methods include focusing exclusively on public hospitals (9), using public hospitals and academic medical centers (26, 27), or using hospital data on uncompensated or Medicaid care to assess hospital safety net involvement (13, 28, 29, 30). Gaskin et al (31) and Hadley and Cunningham (12) blended these various approaches, using public hospitals and a select group of non-profit SNHs with disproportionate provision of care to Medicaid patients to identify SNHs.…”
Section: Methodsmentioning
confidence: 99%